Proceedings of the Genetic and Evolutionary Computation Conference Companion 2021
DOI: 10.1145/3449726.3459579
|View full text |Cite
|
Sign up to set email alerts
|

Option

Abstract: Many platforms for benchmarking optimization algorithms offer users the possibility of sharing their experimental data with the purpose of promoting reproducible and reusable research. However, different platforms use different data models and formats, which drastically inhibits identification of relevant data sets, their interpretation, and their interoperability. Consequently, a semantically rich, ontology-based, machine-readable data model is highly desired.We report in this paper on the development of such… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…They found that factors such as lot size, age of the house, and number of bedrooms and bathrooms were important predictors of housing prices. Similarly, a study by [3][4][5] used EDA to identify the key factors influencing housing prices in Madrid. They found that factors such as location, size of the property, and condition of the building were important predictors of housing prices.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found that factors such as lot size, age of the house, and number of bedrooms and bathrooms were important predictors of housing prices. Similarly, a study by [3][4][5] used EDA to identify the key factors influencing housing prices in Madrid. They found that factors such as location, size of the property, and condition of the building were important predictors of housing prices.…”
Section: Literature Reviewmentioning
confidence: 99%